The Qur’an in Europe, A European Qur’an: A History of Reading, Translation, Polemical Confrontation and Scholarly Appreciation - Tottoli, Roberto (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
The broad interest in the emergence and presence of Islam and Muslims by Europe goes back to the centuries immediately following Muslim conquests and spread through the Mediterranean (from the 1st ce. AH / 7th cen. AD). A number of studies in the previous decades have discussed the perceptions and evaluations of Islam by Europeans from the Middle Ages till modern times, at times focusing on the Qur’an. How the Islamic holy text was known, collected in manuscripts, translated, read, used and polemically discussed in its contents from the 12th century until contemporary times is a chapter of European intellectual activity. Recent research and above all the projects financed by the European commission, which are currently being carried out, are a contribution to the study of the Qur’an and in particular to the history of the presence of the Qur’an in European consciousness. In this field the project “EuQu – The European Qur’an” is particularly significant; it has the ambition to demonstrate how the reading and uses of the Qur’an were important in the intellectual, cultural and religious developments of Europe through the ages.